2021
DOI: 10.1186/s12905-021-01391-5
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle modifications after the diagnosis of gynecological cancer

Abstract: Background The influence of lifestyle factors on the quality of life, incidence and tumor recurrence has been evaluated in several studies and is gaining increasing importance in cancer research. However, the extent of the influence of such lifestyle factors on the quality of life of cancer patients remains largely unclear, as does the number of patients actually pursuing these lifestyle changes. The purpose of this study was to examine the prevalence and predictors of lifestyle changes in pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 47 publications
(60 reference statements)
0
10
0
Order By: Relevance
“…Previous studies reported unmet supportive care and information needs concerning health behaviors such as sports, diet, or relaxation for gynecological and breast cancer patients after primary treatment. 3,34 As these patients show increased motivation to pursue a healthy lifestyle, for example, to gain a feeling of control of cancer recurrence, 35,36 our findings stress the importance of supportive care in this regard.…”
Section: Discussionmentioning
confidence: 57%
“…Previous studies reported unmet supportive care and information needs concerning health behaviors such as sports, diet, or relaxation for gynecological and breast cancer patients after primary treatment. 3,34 As these patients show increased motivation to pursue a healthy lifestyle, for example, to gain a feeling of control of cancer recurrence, 35,36 our findings stress the importance of supportive care in this regard.…”
Section: Discussionmentioning
confidence: 57%
“…1,2 Dietary changes commonly reported by cancer survivors include increased intake of fruits and vegetables and reduced consumption of meats, alcohol, fat, sugar, and dairy products. [3][4][5][6][7] These changes largely align with diet quality recommendations for cancer survivors, 8 and there is evidence that adhering to a high-quality dietary pattern post-diagnosis is associated with better survival and quality of life, particularly among people with breast and colorectal cancer. 9,10 To date, little is known about the dietary practices of women who have completed primary treatment for ovarian cancer.…”
mentioning
confidence: 86%
“…Our study includes a much larger sample of women than previous studies reporting on dietary practices after a diagnosis of ovarian cancer. 4,11 We also examined participants' comments about dietary practices by disease recurrence and treatment status at the time of completing the questionnaire. Furthermore, this study captured information about dietary practices that women "feel is important," but not addressed in the FFQ.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 2 more Smart Citations